Factors That Influence Cybersecurity Compliance Behaviours by Bank Employees: A Case of Banks Operating In Kenya - Wakoli, Leonard W. (International Journal of Scientific Research and Management (IJSRM), 2024)
Digitization of transactions in Banks has developed exponentially since the advent of the internet technology.  This has brought about efficiency and high quality service delivery at all times.  However, cyber threats also continue to grow exponentially in spite of various initiatives to counter the threats.  There are numerous technology initiatives to address the issue of cyber threats but the problem still persists.  There is very limited research on how to leverage on human behaviours to effectively improve Cyber security compliance behaviours in Banks.  Investigating Cyber security Compliance behaviours in Banks has therefore become inevitable. The main purpose of this study was to determine the factors that influence cyber security compliance behaviours in banks operating in Kenya.  This was accomplished using a model that was based on an integration of three theories: Institutional Theory, the Protection Motivational Theory (PMT) and the General Deterrence Theory (GDT).  In order to empirically test the relationships between the independent and dependent variables, data were collected from 75 purposively selected bank employees in Kenya.  The Research was carried out using the mixed (both quantitative and qualitative) approach and survey tools used to collect data were verified for reliability and validity before being used.  Data analysis was carried out using SPSS Version 25.0, MS Excel 2013, and WarpPLS (SEM) Version 7.0.  The findings of our study indicate that the direct paths from the independent variables “Normative pressure” (p = 0.026, β = 0.213), “Self-Efficacy” (p < 0.001, β = 0.440), “Punishment certainty” (p = 0.024, β = 0.217), “Age” (p = 0.013, β = 0.243), “Prior experience with computers” (p = 0.004, β = -0.284) were found to have a positive, direct and significant influence on a bank employee cyber security compliance behaviours. “Top management commitment” was found to partially mediate between self-efficacy and Cyber security compliance behaviours.Bank management may find the results useful for future policy formulation in relation to cyber-security compliance behaviours.  Researchers and scholars may also find the results useful in terms of contribution to the body of knowledge and further investigation to fill the gaps identified by the study.